Nodular Scleritis Associated with Herpes Zoster Virus: An Infectious and Immune-Mediated Process - Mónica Loureiro; Renata Rothwell; Sofia Fonseca (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of anterior nodular scleritis, preceded by an anterior hypertensive uveitis, which was primarily caused by varicella zoster virus (VZV). Case Report. A 54-year-old woman presented with anterior uveitis of the right eye presumably caused by herpetic viral disease and was successfully treated. Two months later, she developed a nodular scleritis and started oral nonsteroidal anti-inflammatory without effect. A complete laboratory workup revealed positivity for HLA-B27; the infectious workup was negative. Therapy was changed to oral prednisolone and an incomplete improvement occurred. Therefore, a diagnostic anterior paracentesis was performed and the polymerase chain reaction (PCR) analysis revealed VZV. She was treated with valacyclovir and the oral prednisolone began to decrease; however, a marked worsening of the scleritis occurred with the reduction of the daily dose; subsequently, methotrexate was introduced allowing the suspension of the prednisolone and led to clinical resolution of the scleritis. Conclusion. This report of anterior nodular scleritis caused by VZV argues in favor of an underlying immune-mediated component, requiring immunosuppressive therapy for clinical resolution. The PCR analysis of the aqueous humor was revealed to be a valuable technique and should be considered in cases of scleritis with poor response to treatment.